KURIKULUM 2013: SPIRITUALISASI SAINS MELALUI PENDEKATAN TEMATIK-INTEGRATIF - Supriyanto Supriyanto (Zawiyah: Jurnal Pemikiran Islam, 2016)
Integration of science discourse revolving around 12 years ago and then spread to almost all religious colleges, both public and private. The concept has been built long enough trouble as realizing the real action, so it is inevitable imagination to this day still immersed several universities in the integration of scientific discourse. The emergence of the curriculum in 2013were judged to have the spirit of integration of the momentum for education practitioners either from early childhood through college. The concept of thematic learning-integrative contained in the new 2013 curriculum limited to internal integration and still mono disciplines, so still need to do the reconstruction of aspects of the curriculum content. Efforts integration of science into the curriculum in 2013 is supported by some models of learning such as project based learning, discovery based learning, inquiry based learning and problem based learning.